Bone Phenotype is Always Present But Androgen Excess is Less Frequently Seen in PAPSS2 Deficiency - Didem Helvacıoğlu; Tülay Güran (Galenos Yayincilik, 2024)
3'-Phosphoadenosine 5'-phosphosulfate synthase 2 (PAPSS2) deficiency is a rare disorder due to biallelic pathogenic variants in the PAPSS2 gene. This disorder was first described in 1998 by Ahmad et al. and Faiyaz ul Haque et al. To date, 79 patients with PAPSS2 deficiency have been reported. The main reported features of these patients are related to bone abnormalities and clinical/biochemical androgen excess. Disproportionate short stature and symptoms associated with spondylar skeletal dysplasia are the most common clinical features that require clinical attention. Androgen excess has been described much less commonly. This review summarizes the currently published clinical, molecular, and biochemical features of patients with PAPSS2 deficiency.